Antimicrobial Susceptibility of Lactic Acid Bacteria Strains of Potential Use as Feed Additives - The Basic Safety and Usefulness Criterion - Stefańska, Ilona; Kwiecień, Ewelina; Jóźwiak-Piasecka, Katarzyna; Garbowska, Monika; Binek, Marian; Rzewuska, Magdalena (Frontiers in Veterinary Science, 2021)
The spread of resistance to antibiotics is a major health concern worldwide due to the increasing rate of isolation of multidrug resistant pathogens hampering the treatment of infections. The food chain has been recognized as one of the key routes of antibiotic resistant bacteria transmission between animals and humans. Considering that lactic acid bacteria (LAB) could act as a reservoir of transferable antibiotic resistance genes, LAB strains intended to be used as feed additives should be monitored for their safety. Sixty-five LAB strains which might be potentially used as probiotic feed additives or silage inoculants, were assessed for susceptibility to eight clinically relevant antimicrobials by a minimum inhibitory concentration determination. Among antimicrobial resistant strains, a prevalence of selected genes associated with the acquired resistance was investigated. Nineteen LAB strains displayed phenotypic resistance to one antibiotic, and 15 strains were resistant to more than one of the tested antibiotics. The resistance to aminoglycosides and tetracyclines were the most prevalent and were found in 37 and 26% of the studied strains, respectively. Phenotypic resistance to other antimicrobials was found in single strains. Determinants related to resistance phenotypes were detected in 15 strains as follows, the aph(3″)-IIIa gene in 9 strains, the lnu(A) gene in three strains, the str(A)-str(B), erm(B), msr(C), and tet(M) genes in two strains and the tet(K) gene in one strain. The nucleotide sequences of the detected genes revealed homology to the sequences of the transmissible resistance genes found in lactic acid bacteria as well as pathogenic bacteria. Our study highlights that LAB may be a reservoir of antimicrobial resistance determinants, thus, the first and key step in considering the usefulness of LAB strains as feed additives should be an assessment of their antibiotic resistance. This safety criterion should always precede more complex studies, such as an assessment of adaptability of a strain or its beneficial effect on a host. These results would help in the selection of the best LAB strains for use as feed additives. Importantly, presented data can be useful for revising the current microbiological cut-off values within the genus Lactobacillus and Pediococcus.